Adaptive neural control of stochastic nonlinear systems with multiple time-varying delays and input saturation - Cui, Guozeng; Jiao, Ticao; Wei, Yunliang; Song, Gongfei; Chu, Yuming (Neural computing & applications, 2014)
This paper investigates the problem of adaptive neural control for a class of strict-feedback stochastic nonlinear systems with multiple time-varying delays, which is subject to input saturation. Via the backstepping technique and the minimal learning parameters algorithm, the problem is solved. Based on the Razumikhin lemma and neural networks’ approximation capability, a new adaptive neural control scheme is developed. The proposed control scheme can ensure that the error variables are semi-globally uniformly ultimately bounded in the sense of four-moment, while all the signals in the closed-loop system are bounded in probability. Two simulation examples are provided to demonstrate the effectiveness of the proposed control approach.